Kajian Hukum Terhadap Partisipasi Perempuan Sebagai Whistleblower Tindak Pidana Korupsi - Nanci Yosepin Simbolon (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2019)
Women's participation in stopping criminal acts of corruption, one of which can be done by becoming a reporter who uncovers a corruption crime that is happening with the aim to improve themselves and stop corruption (whistleblowers). The purpose of this study is to find out how the participation of women as whistleblowers and how the protection provided by the state to women who are whistleblowers of corruption case, so that the authors can assess normatively the advantages and disadvantages so that they can provide input as a contribution to criminal law enforcement of corruption, especially regarding the participation of women as whistleblowers for corruption case. The large and scattered female population in all occupations and government agencies causes women to have a major role in participation in the prevention and eradication of criminal acts of corruption. Legal protection for women who become whistleblowers of corruption must be given extra-strict. Because the nature of female feminism gives women weakness both physically and mentally.